Light-dependent control of redox balance and auxin biosynthesis in plants - Yokawa, Ken (Landes Bioscience, 2014)
Auxin, indole-3-acetic acid (IAA), plays a crucial role for morphogenesis, development, growth, and tropisms in many plant species. Auxin biosynthesis is accomplished via specific pathways depending on several enzymes starting from amino acid, tryptophan. Auxin biosynthesis in maize is particularly active at the tip of coleoptile expressing abundant YUCCA (YUC) protein, which is essential for auxin biosynthesis. In vitro experiment demonstrated that precursor of auxin molecule; indole-3-acetaldehyde (IAAld) was generated by illumination of the mixture of tryptophan and flavin in non-enzymatic manner. In addition, we have detected immediate production of reactive oxygen species (ROS) in illuminated Arabidopsis root cells. In this perspective, we are proposing the non-enzymatic regulation of redox homeostasis and auxin biosynthesis throughout the plant body under variable environmental light conditions.